Notes on Ipomoea L. (Convolvulaceae) in Cuba and neighbouring islands with a checklist of species found in Cuba - Wood, J; Scotland, R (Springer London, 2017)
An updated checklist of species of Ipomoea L. found in Cuba is presented with analysis of the different elements represented. I. alterniflora Griseb. is defined broadly to include I. obtusata Griseb. and I. excisa Urb. and its differences from the little-known I. cubensis (House) Urb. are discussed. I. calophylla C. Wright ex Griseb. is reinstated as the correct name for the species generally known as I. lacteola House. I. praecox C. Wright is recognised as a distinct species from I. argentifolia A. Rich. and images are provided to help distinguish the two species. I. flavopurpurea Urb. and I. dajabonensis Alain are shown to be conspecific with I. longeramosa Choisy, whose disjunct distribution is mapped and discussed. The little-known I. montecristina Hadač is described and illustrated and the cited collections show it to be locally common in the Guantánamo region. I. microdonta J. R. I. Wood & Scotland is described as new from Camagüey in central Cuba. Eight species endemic to Cuba collected by Ekman and described by Urban in 1924 – 25 are evaluated but only two, I. balioclada Urb. and I. erosa Urb., are deemed to warrant recognition as distinct endemic species. The origin and typification of I. horsfalliae Hook. are discussed and an epitype designated. Cultivated plants named I. horsfalliae occur in many tropical countries including Cuba but their extreme variation suggests hybrid origin. Four species from Jamaica, I. rubella House, I. lineolata Urb., I. carmesina Proctor and the Jamaican plant called I. horsfalliae are treated as synonyms of a variable I. lineolata, which is endemic to the island. I. saxicola Proctor is treated as var. saxicola J. R. I. Wood & Scotland of I. ternata Jacq. I. cyanantha Griseb. is treated as a synonym of I. lindenii M. Martens & Galeotti. Lectotypes are designated for I. cyanantha, I. lindenii, I. praecox, I. punctata C. Wright, I. geranioides Meisn. and I. grisebachii Urb.